2006
DOI: 10.1111/j.1469-1809.2006.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between CAG Repeat Length and Age of Onset Differs for Huntington's Disease Patients with Juvenile Onset or Adult Onset

Abstract: SummaryAge of onset for Huntington's disease (HD) varies inversely with the length of the disease-causing CAG repeat expansion in the HD gene. A simple exponential regression model yielded adjusted R-squared values of 0.728 in a large set of Venezuelan kindreds and 0.642 in a North American, European, and Australian sample (the HD MAPS cohort). We present evidence that a two-segment exponential regression curve provides a significantly better fit than the simple exponential regression. A plot of natural log-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 11 publications
1
91
3
1
Order By: Relevance
“…By using variance-components analysis, we have been able to obtain a more precise estimate of the familiality than previous studies have reported (19,20,23). Surprisingly, even after controlling for the effect of allele length, our results indicate that fully 59% of the variability in residual age of onset is familial and attributable to either genetic or shared environmental factors (15 (15).…”
Section: Evidence For Genetic and Environmental Modifierscontrasting
confidence: 45%
See 2 more Smart Citations
“…By using variance-components analysis, we have been able to obtain a more precise estimate of the familiality than previous studies have reported (19,20,23). Surprisingly, even after controlling for the effect of allele length, our results indicate that fully 59% of the variability in residual age of onset is familial and attributable to either genetic or shared environmental factors (15 (15).…”
Section: Evidence For Genetic and Environmental Modifierscontrasting
confidence: 45%
“…Through studying the Venezuelan kindreds, we showed that the length of the CAG triplet repeat is the most important factor in determining age of onset of HD (13, 17,20,22). We wished to discover if other factors, in addition to the size of the CAG repeat, play a role in determining age of onset.…”
Section: Modifiers Of Age Of Onset Of Hd In the Venezuelan Kindredsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with the juvenile variant of HD typically have an age of onset of under 20 years and can have Ͼ70 CAG repeats (Alonso et al 1997;Sanchez et al 1996;Telenius et al 1993). Whereas a strong relationship is found between age at onset and CAG repeat lengths up to ϳ60, the addition of extra CAG repeats above this seems to have little effect (Andresen et al 2007). Indeed, children with highly expanded CAG repeats show very little variation in age of onset, and those carrying repeats between 100 and Ͼ250 CAG repeats present with symptoms at a similar age (Nahhas et al 2005;Nance et al 1999;Papapetropoulos et al 2005;Seneca et al 2004;Wojaczynska-Stanek et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of somatic mosaicism appear to be relatively lower in small alleles than in long alleles owing to the lengthspecific effect. This gives rise to relatively later ages of onset in small alleles than in long alleles, resulting in the observed nonlinear relationship between age of onset and inherited repeat length [14,45].…”
Section: Discussionmentioning
confidence: 99%